Letter: missed opportunities for the diagnosis of colorectal cancer in patients with inflammatory bowel disease—still significant room for improvement. Issue 5 (11th August 2021) - Saitta, Daniel; Garg, Mayur
LINKED CONTENT: This article is linked to Gordon et al paper. To view this article, visit https://doi.org/10.1111/apt.16155